2009
DOI: 10.1126/science.1165995
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Molecular Mobility in Actively Deformed Polymer Glasses

Abstract: When sufficient force is applied to a glassy polymer, it begins to deform through movement of the polymer chains. We used an optical photobleaching technique to quantitatively measure changes in molecular mobility during the active deformation of a polymer glass [poly(methyl methacrylate)]. Segmental mobility increases by up to a factor of 1000 during uniaxial tensile creep. Although the Eyring model can describe the increase in mobility at low stress, it fails to describe mobility after flow onset. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

60
383
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(447 citation statements)
references
References 27 publications
60
383
4
Order By: Relevance
“…31,35 The reason is that the Eyring equation does not take into account the extra shift of the energy barriers with stress due to the flow of the cage itself; the latter leads to stronger acceleration of the dynamics, ultimately leading to yield. 76 The solid-or liquid-like response of the material to the applied stress and hence the validity of eq 7 depends both on the thermal relaxation time τ P 2 and on the strain rate γ.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…31,35 The reason is that the Eyring equation does not take into account the extra shift of the energy barriers with stress due to the flow of the cage itself; the latter leads to stronger acceleration of the dynamics, ultimately leading to yield. 76 The solid-or liquid-like response of the material to the applied stress and hence the validity of eq 7 depends both on the thermal relaxation time τ P 2 and on the strain rate γ.…”
Section: Resultsmentioning
confidence: 99%
“…Following earlier studies 35 we use the rotational relaxation time τ P 2 as the τ R in eq 7. According to Eyring's approach, the applied stress produces linear shifts of the energy barriers surrounding a monomer, thus enhancing monomer diffusion in the direction of stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we show that a minimal model, combining just two key elements of any such theory (nonfactorable aging/rejuvenation, and the strain dependence of polymer-borne stresses), semiquantitatively explains many of the results reported in [3].…”
mentioning
confidence: 94%
“…Particularly striking is the evolution of the segmental relaxation time τ (t), controlling the rate of local rearrangements, when a load is applied. Recently, Lee et al [3,15] showed that τ (t) falls steadily during the early stages of elongational deformation, and then more sharply, reaching a small fraction ∼ 10 −3.3 of its initial level before dramatically rising again, as the local strain rate started to drop on entering the 'strain hardening' regime. While elements of this scenario have been confirmed in coarse-grained and molecular simulations [17][18][19][20], no convincing theoretical picture has yet emerged.…”
mentioning
confidence: 99%